L1 Norm Based Computational Algorithms - Bidabad, Bijan (Bangladesh Journal of Multidisciplinary Scientific Research, 2019)
This paper gives a rather general review of the L1 norm algorithms. The chronology and historical development of the L1 norm estimation theory for the period of 1632-1928 will be surveyed and the algorithms belonging to the after 1928 period will be categorized into three main classes of direct descent, simplex type, and other algorithms.